Assembling reconfigurable endoluminal surgical systems: opportunities and challenges. (4th December 2009) - Nagy, Z.; Fluckiger, M.; Oung, R.; Kaliakatsos, I.K.; Hawkes, E.W.; Nelson, B.J.; Harada, K.; Susilo, E.; Menciassi, A.; Dario, P.; Abbott, J.J.
The success of capsule endoscopy has promoted the development of the next generation of endoluminal surgical devices, and many research groups have proposed robotic capsules with novel functionalities, such as active locomotion and surgical intervention capabilities. Yet, these capsules are still single robotic units with a limited number of components and degrees of freedom. This paper addresses this inherent limitation of single capsule units by introducing the concept of modular robotics for surgical robotics. In the proposed procedure, the modules are ingested and assembled in the stomach cavity. We report on the key technologies of such a system: its self-assembly, actuation, power, and localisation.